CD163 receptor editing for resistance to porcine reproductive and respiratory syndrome virus (PRRSV) - Stoian, Ana Maria Mihaela (Kansas State University, 2020)
Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most economically destructive viruses affecting swine worldwide. In the U.S. alone, annual estimates indicate losses to national swine herds of $664 million. PRRSV isolates can be divided into two different genotypes, PRRSV-1 or PRRSV-2, which share only about 70% identity at the nucleotide level. Previous work showed that pigs lacking CD163 expression on macrophages are protected from PRRSV-2 infection (Whitworth et al., 2016). This receptor is composed of nine scavenger receptor cysteine-rich (SRCR) domains and two proline-serine-threonine (PST)-rich regions, one between SRCR6 and SRCR7, and one between SRCR9 and the transmembrane region and cytoplasmic tail. The purpose of the first study was to identify domains in CD163 that are necessary for infection with a PRRSV-2 isolate. The model system consisted of transfecting HEK cells with plasmids that expressed various CD163 domain deletions and an enhanced green fluorescent protein (EGFP) tag. After two days, the cells were infected with a P129 isolate expressing red fluorescent protein (RFP). The results showed that transfected cells possessing a deletion of the 101 amino acid SRCR5 or disruption of any of the conserved disulfide bonds within SRCR5 of CD163 were resistant to infection. Deletion of the 16 amino acid PSTII domain also has a negative impact on infection. The importance of both SRCR5 and PSTII domains in PRRSV infection indicates that the viral protein complex on the surface of the virion may form multiple contacts with CD163. A recent study showed that CD163 pigs containing a SRCR5 domain swap with the corresponding homolog SRCR8 from the hCD163L1 protein became resistant to PRRSV-1 but not PRRSV-2 (Well et al., 2017), showing that the viruses recognize different peptide sequences within SRCR5. An analysis of various studies that demonstrated the requirement of SRCR5 for PRRSV infection showed that some SRCR5 deletion constructs retained the ability to sustain a low-level of infection when retaining the SRCR4/5 inter-domain region, AHRK. Thus, the purpose of the second study was to identify the minimum changes in SRCR5 and the SRCR4/5 interdomain region sufficient to make HEK cells resistant to infection with both PRRSV genotypes. The results from this study showed that the insertion of proline-arginine (PR) after amino acids 57 and 99 inhibits infection with a PRRSV-1 isolate, whereas PR insertion after amino acids 8, 47, 54 and 99, inhibits PRRSV-2 infection. Furthermore, the deletion of the SRCR4/5 interdomain sequence, AHRK, also blocks infection. A monoclonal antibody (mAb) 2A10 was previously produced by immunizing pigs with porcine alveolar macrophages and has been used in various CD163-related experiments. There is currently no information regarding the location of the epitope recognized by this antibody, therefore, the goal of the last study was to determine this. By western blot analysis, immunofluorescence antibody assay and flow cytometry, we identified SRCR1 as the region recognized by the mAb 2A10. The data presented in this dissertation provided valuable tools for refinement of in vitro receptor editing approaches for prevention of PRRSV or other swine diseases.
Keywords: CD163; PRRSV; SRCR5 domain; PSTII region; mAb 2A10